Altered thresholds for thermoregulatory sweating and vasodilatation in anorexia nervosa. Issue 6245 (4th October 1980) - Luck, P; Wakeling, A
Abstract : The changes in peripheral (hand) blood flow that occurred when deep body temperature was raised were measured in 13 patients with anorexia nervosa and 13 control subjects. The relation between blood flow and core temperature was shifted to the left in the patients with anorexia, with the onset of vasodilatation occurring at lower core and mean skin temperatures: no significant differences in the slopes of the responses were evident. The onset of thermal sweating occurred at lower core and mean skin temperatures in the patients with anorexia than in the controls. After ingestion of a high-energy liquid meal core temperature increased in the patients, and this was accompanied by a significant rise in peripheral blood flow in most cases. A similar meal in the normal subjects was followed by either no change in core temperature or a slight fall, and no consistent change in peripheral blood flow. These findings suggest that the lowering of thresholds for thermoregulatory sweating and vasodilatation may be a contributory factor to the abnormally low core temperature of patients with anorexia and may also explain some of their common complaints relating to feelings of warmth in the hands and feet after meals.